Pyelonephritis and bacteremia caused by Haemophilus parainfluenzae: case-report of an unusual pathogen. Issue 2 (4th March 2021) - Nevejan, Louis; Goegebuer, Truus; Mast, Philippe; Lemmens, Ann
ABSTRACT: We present a case of a young man with known urinary tract abnormalities who developed pyelonephritis and bacteremia caused by Haemophilus parainfluenzae. Since routine urine culture usually does not include enriched media for Haemophilus spp., the true incidence of urinary tract infections caused by H. parainfluenzae is currently unknown. Our case, however, demonstrates that H. parainfluenzae is a potential urinary pathogen, at least in patients with urinary tract anomalies. Clinical laboratories should consider expanding their culture efforts to detect unusual pathogens in patients with underlying risk factors.